(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2012)
This paper discusses the situation of art criticisms and art writings in Malaysia. Although Malaysian artists have moved into contemporary art practices, the exhibition strategies adopted by private galleries, including the national gallery have not changed significantly for the last fifty years. Curatorial practices have been regarded as unimportant, resulting in repetitive and limited ways of presenting art works. Consequently, art exhibitions tend to be a cluster of work assembled in a gallery premise, and usually connected by a very loose theme. Often art essays are published in conjunction with the exhibitions. Since research papers on contemporary art are limited, the essays or writings published in the exhibition catalogues become an important source of reference on Malaysian art, and they have been referred to as "art writings". Besides the lack of proper "art writings", there is also a problem with "art criticism" in the country. The lack of professional art critics and the multiple roles played by writers, artists, art historians and arts manager are among the main reasons for the present art criticism and art writing scenario in the country.